Level of Community Knowledge on Preventive Measures for Dengue Hemorrhagic Fever in Sungai Laur Public Health Center Area - Triyuni Lestari; Gabby Novikadarti Rahmah; Ikbal Fradianto (Critical Medical and Surgical Nursing Journal, 2026)
Introduction: In 2023, a total of 12 cases of Dengue Hemorrhagic Fever (DHF) were reported in the Sungai Laur Public Health Center area, accompanied by a low larval-freerate (ABJ) of 33.33%. This condition indicates a high risk of dengue transmission due to thepresence of mosquito breeding sites. Community knowledge plays a crucial role inpreventing and controlling DHF, as informed individuals are more likely to engage ineffective vector control practices. Therefore, this study aimed to assess the level ofcommunity knowledge regarding DHF prevention in the Sungai Laur Public Health Centerarea. Methods: This study employed a quantitative cross-sectional design. The samplingtechnique used was accidental sampling, involving 92 respondents residing in the SungaiLaur Public Health Center area. Data were collected using a structured questionnaire thatmeasured respondents’ knowledge related to DHF prevention strategies, includingenvironmental management and mosquito control measures. Data analysis was conductedusing univariate analysis to describe the distribution of knowledge levels amongparticipants. Results: The findings revealed that the majority of respondents, 54 individuals (58.7%),demonstrated good knowledge regarding DHF prevention. Meanwhile, 38 respondents(41.3%) were categorized as having poor knowledge. These results indicate that althoughmore than half of the community possesses adequate knowledge, a substantial proportionstill lacks sufficient understanding. Conclusion: Overall, the community in the Sungai Laur Public Health Center area shows arelatively good level of knowledge regarding DHF prevention. However, continuous effortsfrom health service personnel are essential to monitor, educate, and promote sustainablepreventive behaviors to further reduce the risk of DHF transmission.